Elective neck dissection during salvage total laryngectomy – a beneficial prognostic effect in locally advanced recurrent tumours. (February 2015) - Hilly, O.; Gil, Z.; Goldhaber, D.; Amit, M.; Biadsee, A.; Popovtzer, A.; Shvero, J.; Cohen, J.; Fliss, D.; Feinmesser, R.; Bachar, G.
<x xml:space="preserve">Abstract</x> Objectives Elective neck dissection during salvage laryngectomy is controversial. The goal of our study was to evaluate the effect of elective neck dissection during salvage laryngectomy in patients with locally advanced disease at recurrence. Design Multicentre, retrospective study. Settings Two tertiary medical centres. Participants Eighty‐seven patients treated by salvage laryngectomy. Main outcome measures Disease‐Free and Overall Survival. Results Fifty‐seven patients underwent salvage total laryngectomy for locally advanced recurrent squamous cell carcinoma of the larynx, and 30 patients underwent salvage laryngectomy for limited recurrent disease. Elective lateral neck dissection was performed in 48 patients. The groups were similar in age, sex, initial TNM stage and pre‐operative treatment. Survival analysis showed that both disease‐free survival and overall survival were improved in patients with locally advanced disease who underwent elective neck dissection. This beneficial effect was not demonstrated in patients with limited disease at recurrence. Multivariate analysis showed that the extent of the recurrent disease as well as elective neck dissection was associated with improved disease‐free survival and overall survival. Conclusions Elective neck dissection during salvage total laryngectomy seems to improve survival in patients with advanced local disease at recurrence. The role of neck dissection in the treatment of smaller tumours awaits further studies.